Evaluation of the relationship between body discomfort and personal background among restaurant cooks - Fazilah, Abdul Aziz; Muhammad Amirul Aizad, Rohizad (Springer, Cham, 2024)
Musculoskeletal disorders (MSDs) carry a heavy socioeconomic burden, and the repetitive movements and heavy physical labor involved in the kitchen make it a high-risk occupation for MSDs. The aim of this study was to evaluate the prevalence of work-related musculoskeletal disorders (WMSDs) in local cooks and to explore their association with personal background. In this cross-sectional study, 100 cooks in restaurants of Pekan Pahang were randomly selected and studied. Data was collected by Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) through interviews with cooks at their workplace. The majority reported musculoskeletal discomforts localized in the upper back, lower back, neck, back, and shoulder and the minimal discomforts were in part of wrist. On the other hand, personal background had in-significant effect on increasing musculoskeletal discomforts of body regions such as upper back, lower back, neck, back, and shoulder (p > 0.005). The findings relating to these factors add new knowledge to our understanding of MSDs in the restaurant and food service industry. However, most restaurant cooks had a high prevalence of musculoskeletal disorders in the upper body. In this context, some considerations are needed for future studies to identify occupational risk factors, including psychosocial and improving working conditions to reduce MSD symptoms among cooks.